Contactos interior-zonas costeras durante la Edad del Hierro: los focos del noreste y suroeste meseteños - Cabanes, EMILIO; Cerdeño Serrano, María Luisa; García Huerta, Rosario; Baquedado, Isabel (Complutum, 1996)
Sin resumen